2018
DOI: 10.1101/303057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limited Introgression Supports Division of Giraffe into Four Species

Abstract: 17All giraffe (Giraffa) were previously assigned to a single species (G. camelopardalis) and nine 18 subspecies. However, multi-locus analyses of all subspecies have shown that there are four 19 genetically distinct clades and suggest four giraffe species. This conclusion might not be fully 20 accepted due to limited data and lack of explicit gene flow analyses. Here we present an 21 extended study based on 21 independent nuclear loci from 137 individuals. Explicit gene flow 22 analyses identify less than one … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The program STRUCTURE was previously used to infer genetic structure in giraffe populations, using either genotypes from 14 microsatellite loci of 381 individuals [29] or PHASED alleles of seven introns for 105 giraffes [38] or rather the extended dataset of 21 introns for 137 individuals [12]. Brown et al [29] suggested the existence of at least six species, but the optimal K was not determined using either the method of Evanno et al [50] or that of Pritchard et al [44], and their results are not reproducible, because the microsatellite data were not made available.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The program STRUCTURE was previously used to infer genetic structure in giraffe populations, using either genotypes from 14 microsatellite loci of 381 individuals [29] or PHASED alleles of seven introns for 105 giraffes [38] or rather the extended dataset of 21 introns for 137 individuals [12]. Brown et al [29] suggested the existence of at least six species, but the optimal K was not determined using either the method of Evanno et al [50] or that of Pritchard et al [44], and their results are not reproducible, because the microsatellite data were not made available.…”
Section: Discussionmentioning
confidence: 99%
“…Seven giraffe datasets were generated for our analyses using the sequences available in the NCBI nucleotide database: the mtDNA-G507 dataset, which contains a mitochondrial fragment covering the whole cytochrome b ( Cytb ) gene and the 5‘part of the control region (length = 1742 nucleotides [nt]) for 507 individuals (listed in Appendix B1.1), and its reduced version including only the 82 different mitochondrial haplotypes, named mtDNA-GH82; the mtDNA-GH82O3, in which the mtDNA-GH82 dataset was aligned to three outgroup species: Bos taurus (NCBI accession number KT184464); Ovis canadensis (NC_015889) and Okapia johnstoni (JN632674) (length = 1776 nt); a nuclear dataset, named nuDNA-G274, including 274 phased alleles of 21 introns (ACP5, C1orf74, CCT2, COL5A2, CTAGE5, CWF19L1; DDX1, DHX36, IGF2B1, MACF1, NOTCH2, NUP155, OTOF, PLCE1, RASSF4, RFRC5, SAP130, SOS1, UBN2, USP33, USP54) for 137 giraffes (accession numbers LT596685-LT598170, MG257969–MG262280); the nuDNA-G274O6, in which the nuDNA-G274 dataset was aligned to the alleles of three outgroup species: the okapi ( Okapia johnstoni , published sequences [12,38]), and two bovid species, (i) Bos taurus , for which the sequences were extracted by BLAST from the whole genome version UMD3.1.1 (http://bovinegenome.org/) or, in case of unavailability of certain genes, from the genome of Bos mutus available on NCBI (SAMN08580377); and (ii) Ovis canadensis , for which the sequences were extracted by BLAST from the genome available on NCBI (CP011888.1); the nuDNA-G137 dataset, comprising the alignments of original consensus sequences of 21 introns for the 137 giraffes (length = 16968 nt), which were recovered by detecting heterozygous sites in Geneious R10 (Biomatters, Auckland, New Zealand); the nuDNA-G137O3 dataset, in which the nuDNA-G137 dataset was aligned to the three outgroup species mentioned above (length = 17276 nt); the nuclear haplotype dataset, named nuDNA-GH274, which was inferred from the nuDNA-G274 dataset using the PHASE v2.1 algorithm implemented in the software DNASP v5.0 [39] (length = 1362 nt; it contains only the sites found to be variable between giraffe haplotypes). All alignments generated for this study were deposited in DRYAD (entry doi: XXXXXXX).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations